ASPECTS OF LIVER ECHINOCOCCOSIS SURGERY - К. Рахманов; Ж. Раджабов; С. Давлатов; Б. Хамдамов; С. Янченко; Р. Наврузов (Bukovynian State Medical University, 2024)
According to the WHO, «...at any given time, more than 1 million people worldwide are aff ected by echinococcosis...». Due to the lack of tendency to decrease the number of patients and the existence of endemic regions where the incidence rate varies from 1.2 to 9.0 per 100,000 population, this parasitic disease continues to be a serious medical and social problem. At the present stage, the diagnosis of echinococcosis does not present signifi cant diffi culties, mainly due to the emergence of non-invasive imaging methods, the informative value of the complex application of which reaches 95-100 %. Aim of the study. Improving the treatment results of patients with liver echinococcosis. Research materials. The study included 328 patients with liver echinococcosis admitted to the surgery department of the multidisciplinary clinic of the Samarkand State Medical University in the period from 2005 to 2023. Depending on the choice of treatment, the patients were divided into two groups: the comparison group consisted of 154 (46.9 %) patients treated from 2005 to 2012 and the main group included 174 (53.0 %) patients operated on from 2013 to 2023. Research results. Compared with the comparison group, in the main group of patients, intraoperative complications decreased from 6.5 to 2.3 %, and complications in the early postoperative period from 18.2 to 5.2 %. In the late postoperative period, the recurrence of the disease decreased from 16.2 % to 3.6 %. Conclusions. The introduction of improved surgical instruments into practice - a modifi ed puncture needle, a «basket clamp» allowed to level the risk of seeding of surrounding tissues with embryonic elements. The introduction of a device for the purpose of identifying hidden biliary fi stulas in the residual cavity after echinococcectomy from the liver reduced the number of bile leaks. With the introduction of a modifi ed method for eliminating the residual cavity after echinococcectomy from the liver, the number of complications during surgery and in the early postoperative period was minimized.